PENGARUH MARKETING MIX (7P) TERHADAP KEPUTUSAN PEMBELIAN SEPEDA MOTOR HONDA, (STUDI KASUS PADA DEALER MOTOR HONDA PT. TUNAS DWIPA MATRA MELAWI) - Ery Niswan; Rindi Astuti (Prodi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Panca Bhakti, 2022)
This study aims to determine how much influence the 7P marketing mix has on the decision to purchase a Honda Vario125 motorcycle at PT. Tunas Dwipa Matra Melawi. In this study, it consists of two variables, namely the 7P independent marketing mix variables (product, price, place, promotion, people, process, and physical evidence), while the dependent variable is the product purchase decision. This researcher uses descriptive analysis with a quantitative approach. The sampling technique used purposive sampling using the Lemeshow formula (1997) in Murti (2013) obtained a sample size of 96.04 rounded to 100 to facilitate research. Collecting data using interview techniques, questionnaires, and documentation studies. Distribution of questionnaires using a questionnaire. The analytical tools in this study are validity test, reliability test, average test, interval class range, multiple regression test, classical assumption test (normality, heteroscedasticity, multicollinearity), and hypothesis test (t test, f test, and coefficient of determination test ). The results of this study indicate that partially or the 7P marketing mix t test does not fully influence the decision to purchase a Honda Vario 125 motorbike, based on the t test only the product indicator (X1) has a significant effect on the purchasing decision of the Honda Vario 125. Meanwhile, simultaneously or test f shows that there is an influence of the 7P marketing mix variable on the purchasing decision of the Honda Vario 125, while the magnitude of the influence based on the coefficient of determination test is 23.8%.